Effect of cationic asphalt emulsion as an admixture on transport properties of roller-compacted concrete. (28th February 2018) - Dareyni, Mohammad; Mohammadzadeh Moghaddam, Abolfazl; Delarami, Aref
Highlights: Cationic asphalt emulsion(CAE) was used as an admixture in RCC. Transport properties of CAE-containing RCC were investigated. ANOVA and intrinsically linear regression were used to evaluate results of tests. The SEM images were employed to interpret the results. If CAE is added equal to 4% or more, transport properties would be improved. Abstract: This study aims to investigate the effect of cationic asphalt emulsion (CAE) as an admixture on durability characteristics of roller compacted concrete (RCC). To this aim, the CAE was added to the RCC mixture at 0%, 2%, 4%, 6%, 8%, and 10% of the cement mass; these mixtures were designed by the maximum density method according to ASTMD1557 . The cubic and cylindrical specimens were fabricated using vibrating hammer; water absorption, sorptivity, water penetration depth, and electrical resistivity tests were conducted to evaluate the durability of the mixtures. The water penetration test was carried out on cubic specimens in accordance with BS EN 12, 390-8: 2009; moreover, by cutting each cylindrical specimen, two 100 × 50 mm discs for conducting sorptivity and one 100 × 100 mm cylinder for conducting the water absorption and electrical resistivity tests were prepared. The results indicated that the decrease in the water absorption, penetration and sorptivity, and the increase in the electrical resistivity of the mixtures can be obtained by increasing the CAE content. Also, the analysis of variance (ANOVA) at 95% confidence level based on Dunnett comparison procedure denoted a significant improvement in the RCC transport properties by adding CAE. Scanning electron microscope (SEM) images were studied and it was revealed that filling the capillary pores and coating the inner surface of larger pores with asphalt exhibited a change in the structure of cement paste pores and demonstrated an improvement in the transport properties of the RCC. Performing electrical resistivity test is of great importance for evaluating the durability of concrete due to its non-destructive and rapid properties. Therefore, intrinsically linear regression models were estimated between its results and other durability indicators, which show proper fits based on their coefficient of determination (minR 2 > 0.83). The findings revealed that electrical resistivity test can be employed to estimate the various transport properties of the RCC.